The Impact of Work Environment Quality, Skill Development, and Leadership on Employee Engagement in Manufacturing Companies in West Java - Judijanto, Loso; Zulfikri, Agung (West Science Journal Economic and Entrepreneurship, 2024)
This study examines the effects of leadership, skill development, and work environment quality on employee engagement in manufacturing companies in West Java. With the manufacturing sector facing high demands for productivity and workforce stability, understanding these factors is critical to enhancing employee motivation and commitment. A quantitative approach was employed, involving a sample of 150 employees, and data were analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS). The results indicate that leadership has the strongest positive influence on employee engagement, followed by skill development and work environment quality. Leadership was found to play a central role in fostering a supportive environment, underscoring the importance of transformational practices in motivating employees. The findings suggest that companies can enhance engagement by investing in leadership development, continuous skill enhancement, and a high-quality work environment. These insights provide valuable implications for manufacturing companies seeking to improve employee engagement and overall organizational performance.